2013
DOI: 10.1177/193758671300600305
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Testing of Interactive Hospital Spaces to Meet the Needs of Waiting Children

Abstract: Design process, healing environments, hospital, interdisciplinary, pediatric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…Guides organizations to create annual goals for integrating engaged care practices [15]. Published January 31, 2017…”
Section: Pfccpartners' Workplanmentioning
confidence: 99%
“…Guides organizations to create annual goals for integrating engaged care practices [15]. Published January 31, 2017…”
Section: Pfccpartners' Workplanmentioning
confidence: 99%
“…The interactive media system evaluated in this study were designed in response to the client‐, family‐ and clinician‐identified needs for accessible and safe play opportunities for clinic waiting spaces. It was designed with input from young people (with and without disabilities), families, clinicians, researchers, designers, building services, and senior management . Clear cause and effect, and absence of predefined goals, maximized cognitive accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the interactive media (depicted in Fig. ), which feature a digitized forest scene, followed a participatory design approach engaging clinic staff, families, and hospital administrators, and is detailed in previous work . It has three design features that differentiate it from toys/electronic games previously studied, as follows .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on healthcare environments demonstrates how aspects of specific interior spaces, such as hallways, lobbies, waiting areas, NICUs, and patient rooms, significantly influence the perceptions and experiences of hospitalized children and their families (Adams, Theodore, Goldenberg, McLaren, & McKeever, ; Biddis, McPherson, Shea, & McKeever, ; Sadler & Joseph, ). Studies also reveal that children and adolescents have clear preferences in terms of the design and features of hospital settings in which they spend time (Coad & Coad, ; Coyne & Kirwan, ; Park, ).…”
Section: Introductionmentioning
confidence: 99%